David i fortællingen i verden - Hasselbalch, Trine Bjørnung (Dansk Teologisk Tidsskrift, 2013)
Interpretations of the narratives about David in the Books of Samuel can be divided roughly into works that understand them one way or the other as products of history, and works that tend to disregard questions about their historical conditions. But neither strategy – studying the meaning of their production in terms of history, or not at all – can bring out all facets in the meaning of producing these narratives. Here a spatial approach is taken, according to which the production of literature is not simply caused by historical contexts that can be accounted for in research; it takes place in unresolved social situations of which the authors are not in control. From this perspective, some nuances are suggested about how the writing of the David narratives could be meaningful to their author(s).